Leadership styles and relational energy: Do all leaderships styles generate and transmit equal relational energy? - Okechukwu E. Amah (South African Journal of Business Management, 2018)
Background: Despite the espoused importance of relational energy, and the fact that it is generated in interaction between leaders and their subordinates, little is known about which leadership style generates the highest relational energy.Objectives: The purpose of this study was to determine if there are differences in the levels of relational energy generated and transmitted when employees interact with leaders who exhibit autocratic, transactional, transformational and servant leadership styles.Method: The study utilised scenario-based experimental methodology to gather data. Five leadership experts reviewed the description of each leadership style prior to use in the study. A pilot study was carried out with 40 executive education participants to establish that the description of each leadership style was different and identifiable by non-experts. Fifty-two executive Master of Business Administration (MBA) participants from various organisations in six industries in Lagos, Nigeria, provided data for the scenario analysis. To avoid errors, the data for each style were collected separately. Data analysis was performed using analysis of variance and Tukey's honest significant difference test.Results: The results of the scenario analysis showed that indeed there is a difference in the relational energy generated when employees interact with different leadership styles.Conclusion: The results have practical implications for the selection and training of individuals to be placed in leadership positions. Leadership selection and training must emphasise servant leadership. This is the first study to empirically establish that different leadership styles generate and transmit different levels of relational energy during interaction with employees.
Keywords: 650